A qualitative enquiry of health care workers' narratives on knowledge and sources of information on principles of Respectful Maternity Care (RMC). - Adelaide M Lusambili; Stefania Wisofschi; Terrance J Wade; Marleen Temmerman; Jerim Obure (Public Library of Science (PLoS), 2023)
Research from sub-Saharan Africa indicate that many women experience varied forms of disrespectful maternity care, which amount to a violation of their rights and dignity. Notably, there is little research that sheds light on health care workers (HCWs) training and knowledge of principles of respectful maternity care (RMC). Formulating appropriate interventional strategies to promote the respectful provision of services for women during pregnancy, childbirth, and postpartum period requires an understanding of the current state of knowledge and sources of information on respectful maternity care among HCWs. This paper reports findings from a qualitative study that examined the knowledge and sources of information on the Respectful Maternity Care Charter among HCWs in rural Kisii and Kilifi counties in Kenya. Between January and March 2020, we conducted 24 in-depth interviews among HCWs in rural Kisii and Kilifi health facilities. Data were analyzed using a mixed deductive and inductive thematic analysis guided by Braun's [2006] six stages of analysis. We found that from the seven globally accepted principles of respectful maternity care, at least half of the HCWs were aware of patients right to consented care, confidentiality and privacy, and the right to non-discriminatory care based on specific attributes. Knowledge of the right to no physical and emotional abuse, abandonment of care, and detentions in the facilities was limited to a minority of health care workers but only after prompting. Sources of information on respectful maternity care were largely limited to continuous medical and professional training and clinical mentorship. The existing gap shows the need for training and mentorship of HCWs on the Respectful Maternity Care Charter as part of pre-service medical and nursing curricula and continuing clinical education to bridge this gap. At the policy level, strategies are necessary to support the integration of respectful maternity care into pre-service training curricula.